Design And Fabrication Of Ankle Foot Orthosis Utilising 3d Scanner And 3d Printing - Ong, Yong Shien (Universiti Sains Malaysia, 2021)
In this research, two types of AFOs which are Solid AFO and Free Motion AFO are designed and fabricated utilizing 3D scanning and 3D printing techniques. The major difference between the two designs is that Solid AFO is made of one solid part. The back of the Solid AFO is covered completely and thus allow no ankle motion. For Free Motion AFO, it is equipped with flexure joints which allows plantarflexion and dorsiflexion at the ankle. The process began with the 3D scanning process using an iPad and Structure sensor. Several intermediate processes are performed such as mesh cleaning, CAD design, slicing and calibrations before proceeding with 3D printing using fused deposition machining (FDM) printer. The part orientation is varied with four different orientations (flatwise, sidewise, 45 degrees upright with normal support and 45 degrees upright with tree support) and the performance of each orientation is studied. Orientation 4 (45 degrees upright with tree support) is selected as the optimum orientation due to the optimum material consumption (40 gram and 13.44 meters) and print time (10 hours and 36 minutes), as well as the outperform quality. Finite element analysis is performed to study the behaviour of the designs under static and dynamic loadings. Static structural analysis is performed to replicate the behaviour of the AFO designs under static loading conditions as the result of the ground reaction forces exerted on the AFO by the ground. On the other hand, transient structural analysis is performed by considering the real-time force applied to the AFO at different tibia angles with respect to four stages of the stance phase (loading response stage, mid-stance stage, terminal stance stage and pre-swing stage).